EFEKTIVITAS BOOKLET STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN TERHDAP HASIL BELAJAR PESERTA DIDIK FASE F SMA 2 ADABIAH PADANG - Fransiska, Sherli; Syamsurizal, Syamsurizal; Fuadiyah, Sa’diatul; Fajrina, Suci; Gusti, Utari Akhir (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Background: Booklets can be produced through development research using the 4D model which consists of define, design, develop, and disseminate stages. Utari Akhir Agusti has developed a booklet until the develop stage, so further research is needed at the disseminate stage by conducting an effectiveness test as one of the steps of the disseminate stage. Methods: This research is a quasi-experiment research with Pretest-Posttest Control Group Design. The population of this study were all students of class XI phase F SMA Adabiah 2 Padang. The sample was taken using simple random sampling technique, so that phase F2 was selected as the experimental class and phase F5 as the control class. Research data in the form of learning outcomes of students in the cognitive domain. Data collection techniques using test techniques. The research instrument is a multiple choice test that has been valid and reliable. The data obtained were analyzed using the t test. Results: Based on the results of research on the cognitive domain shows the average value of the experimental class is higher than the control class. Data analysis using paired sample test, obtained sig value (0.000) < α value (0.05). Thus it can be concluded that the booklet of the structure and function of plant tissues effectively improves the learning outcomes of phase F students of Adabiah 2 Padang High School. Conclusion: Based on the research that has been done, it can be concluded that the booklet of the structure and function of plant tissues effectively improves the learning outcomes of phase F students of Adabiah 2 Padang High School.